Pattern of mental distress among chronic disease subjects in urban Puducherry, India - Kalaiselvi Selvaraj; S Ganesh Kumar; Akkilagunta Sujiv (Wolters Kluwer Medknow Publications, 2015)
Aim: Limited information is available on the status of mental distress among chronic disease subjects attending primary care settings in India. This study aimed to assess the pattern of mental distress among chronic disease subjects. Materials and Methods: This facility based cross-sectional study was carried out among chronic disease subjects attending urban health center attached to a Medical Institution in Puducherry, India. Mental distress was assessed by general health questionnaire-12. Data on associated factors were collected by structured questionnaire. Results: Mean age of the subjects was 58.2 ΁ 12.8 years. Around 80% of the subjects found to have mental distress. Mental distress was comparatively more among females, educated more than middle school, person living in the nuclear family and suffering from joint pain (P < 0.05). Subjects who had both diabetes and hypertension reported more mental distress. Females had comparatively more mental distress after adjusting for potential confounders. Conclusion: Mental distress among chronic disease subjects in this setting is high especially among females screening of this high-risk group may help in taking appropriate interventional measures.